Improvement of Communications in Labor Market During Primary Profiling of Workforce - Batiuk , Anna (Theory and Practice of Public Administration, 2019)
A productive and effective employment of the population and long-term unemployment depend on a quality communication strategy. Communications in the labor market are the basis of the interrelations between the workforce and their employers. Personal qualities and psychological condition of employment service clients affect the quality of the services and their job placement. A rapid development of information and communications technologies has brought new challenges to the labor market. As a result, the risk of workforce deficit is increasing, and the unemployment is rising. In 2018, an individual approach to service delivery and profiling of personal needs was implemented, and a new category of specialists – ‘a career advisor’ – was introduced. A career advisor works individually with every client. The interaction of the client and the career advisor is built on the basis of their common goal – job placement. For productive and effective employment of the population, it is necessary to arrange a coherent work of the career advisor, a consultant to employers, and measures of active state employment policy, which is possible with a strategy of efficient communications. During the procedure of profiling, a contact between a specialist of an employment center and the unemployed is established, which affects directly all further work, facilitating employment. At this stage, it is necessary to achieve the interaction and understanding between the client and the employment service specialist. There are barriers that get in the way of reaching consensus by the interlocutors, in particular: moral and psychological patterns of individuals, distrust in employment centers efficiency etc. In order to reach mutual understanding, it is appropriate to apply psychological methods, i.e. reproduce the behavior, phraseology, intonations, and gestures of the partner. Servicing clients at the employment center should not be burdened with excessive formalism. A specialist of employment service should determine the abilities of a client and their needs. The State Employment Service must create additional employment opportunities and establish itself as a reliable partner in the job placement sphere.